NOTAS SOBRE FLEBOTOMIDOS AMERICANOS DIPTERA PSYCHOD - DAMPF, ALFONSO (Instituto de Salubridad y Enfermedades Tropicales, CD MEXICO, DF, MEX, 1926)
The content of folic acid in human cardiac muscle was detd by the method of Teply and Elvehjem, using Streptococcus faecalis No difference between normal and diseased hearts was found The avg concn of free folic acid was 081 m[mu]g/g of muscle a
REV ENT [RIO DE JANEIRO]
Keywords: NOTAS, FLEBOTOMIDOS, AMERICANOS; CIENCIAS MEDICAS